(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
There is a question every English teacher should think about. Does the current English teaching system or the patterns meet the requirements of the vibrant, dynamic era that we are living in? The present era demands that a person should think in a creative, innovative, and independent way and has excellent interpersonal and communicative skills. Teachers of English often make great efforts to focus students on the target language so that they have all the tools they need to use the language effectively in their lives. English teachers spend hours preparing lessons, finding creative ways of introducing different aspects of the language through new materials, and so on.